ENHANCING THE STUDENTS’ READING COMPREHENSION USING PRE-QUESTIONING IN PERSONAL RECOUNT TEXT - Suwarni, Andi (Corolla International Conference, 2022)
The objective of research was to find out the students’ achievement in reading comprehension through pre-questioning in personal recount text at the tenth grade students of SMA Negeri 3 Watampone. The scope of the study is the writer focused to enhance the students’ achievement in literal reading (main idea, detail information and following instruction) and the students’ achievement in interpretative comprehension (drawing conclusion). This research follows the principal working of Classroom Action Research (CAR) that contains of four stages they are: planning, implementation of action, observation, and reflection. This research was conducted at SMA Negeri 3 Watampone for English subject. As subject in this research was the tenth grade for 2020-2021 academic years. The class consisted of 30 students. And the instrument used reading test was used at the end of every cycle by using criteria of reading test to measure students’ reading comprehension and observations was used to measure the students’ participation during the teaching and learning process by using pre-questioning strategy. Based on the the research findings, the researcher comes to the following conclusions as follow; the use of pre questioning in personal recount text in presenting the reading comprehension material at the tenth grade students of SMA Negeri 3 Watampone improve the students’ achievement. The findings indicate that the mean score of test in Cycle II is greater than the mean score of test for Cycle I (67.75> 51.31). Therefore the use of pre questioning in personal recount text can improve the students’ literal and interpretative comprehension the tenth grade students of SMA Negeri 3 Watampone (31.40% from Cycle I to Cycle II).